Analisis Bauran Komunikasi Pemasaran pada Bisnis Usaha Kerupuk Babi Ajong - Reinardus, Mitchelle; Aulia, Sisca (Kiwari, 2024)
As time went by, many culinary enthusiasts began to open their own culinary businesses. The role of marketing communications is very important because marketing communications is an aspect of marketing success. This research aims to analyze the marketing communications carried out by Ajong Pork Crackers to increase sales, as well as the challenges in maintaining the Crackers product. Ajong Pig. This research adopts a qualitative approach to understand and analyze marketing communications used in promoting the product "Ajong Pork Crackers". In this research, the researcher chose to use an in-depth interview method to obtain the required data. The interview used in this research was a semi-structured interview ( semistructured interview). The results of this research indicate that marketing communications for Ajong Pork Crackers consists of three main aspects: segmentation, targeting, and positioning. Segmentation is very important because it helps companies understand consumer needs, preferences and behavior. The target in marketing "Ajong Pork Crackers" can involve appropriate market segmentation. Maybe it can be aimed at consumers who are looking for alternative snacks with a distinctive taste. Positioning is also very important for "Ajong Pork Crackers" to focus on the unique taste that differentiates this product from other pork crackers. Ajong Pork Crackers applies the marketing concept (marketing mix) which is usually called 9P including product, price, promotion, place, people, process, physical evidence, packaging, and public relations. Dengan berjalannya waktu, banyaknya peminta kuliner mulai membuka usaha kulinernya sendiri. Peran komunikasi pemasaran sangatlah penting karena komunikasi pemasaran adalah aspek dari suksesnya pemasaran. Penelitian ini bertujuan untuk menganalisis komunikasi pemasaran yang dilakukan oleh Kerupuk Babi Ajong untuk meningkatkan penjualan serta tantangan dalam mempertahankan produk Kerupuk Babi Ajong. Penelitian ini menggunakan pendekatan kualitatif dan metode wawancara mendalam untuk mendapatkan data yang dibutuhkan. Hasil penelitian ini menunjukkan bahwa komunikasi pemasaran Kerupuk Babi Ajong terdiri dari tiga aspek utama: segmentasi, target, dan positioning. Segmentasi sangat penting karena membantu perusahaan memahami kebutuhan, preferensi, dan perilaku konsumen. Target dalam pemasaran “Kerupuk Babi Ajong “ dapat melibatkan segmentasi pasar yang tepat. Mungkin dapat ditujukan kepada konsumen yang mencari alternatif camilan dengan rasa yang khas. Positioning juga sangat penting untuk “Kerupuk Babi Ajong “ untuk memfokuskan pada keunikan rasa yang membedakan produk ini dari kerupuk babi lainnya.Kerupuk Babi Ajong menerapkan konsep pemasaran (bauran pemasaran) yang biasa disebut 9P diantaranya produk, harga, promosi,tempat, orang, proses, bukti fisik, pengemasan, dan hubungan masyarakat.